The Effect Of Per Capita Income, Bi Rates And Consumer Price Index On The Demand For Electronic Money In Indonesia 2009-2022 - Akbar, Januaril; Syapsan, Syapsan; Endang Kurniasih, Cut (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study aims to analyze the effect of per capita income, Bank Indonesia (BI) interest rates, and the consumer price index on the demand for electronic money in Indonesia during the period 2009-2022. In an increasingly developing digital economy era, financial technology (FinTech) innovations play a crucial role in facilitating financial transactions and fostering a cashless society. This study highlights macroeconomic variables that are considered to have a significant impact on the adoption of electronic money in Indonesia.The data used in this study consists of annual data obtained from official sources such as Bank Indonesia and the Central Bureau of Statistics. The analysis method used is multiple linear regression to measure the effect of each independent variable on the dependent variable. Before performing the regression analysis, classical assumption tests were conducted to ensure that the data met the classical linear regression requirements, including tests for normality, multicollinearity, autocorrelation, and heteroscedasticity.The results of the study indicate that per capita income has a positive and significant effect on the demand for electronic money. This finding suggests that an increase in per capita income encourages greater use of electronic money as a means of payment. BI interest rates were also found to have a significant but negative effect on the demand for electronic money, indicating that higher interest rates tend to reduce the use of electronic money. Conversely, the consumer price index was found to have a positive but not significant effect on the demand for electronic money, meaning that fluctuations in consumer prices do not have a substantial impact on the use of electronic money.